An investigation on microstructure and mechanical behaviour of copper-nickel coated carbon fibre reinforced aluminium composites. (25th November 2020) - Gajalakshmi, K; Senthilkumar, N; Mohan, B; Anbuchezhiyan, G
Abstract: In the present investigation, mechanical, corrosion and fatigue characterization is performed on the fabricated aluminium metal matrix composite (AMMC), by reinforcing nickel (Ni) and copper (Cu) coated 4% carbon fibre (CF) in aluminium alloy (AA6026) matrix. With a view of enhancing the strength of the aluminium alloy, an optimal percentage (4 wt%) of CFs is reinforced; as CFs cannot be directly reinforced in the aluminium matrix due to poor wettability, CFs are coated with Ni and Cu using electroless plating technique for better wettability and bonding between reinforcement and matrix. Properties of the cast alloy and coated CF reinforced composite are compared and the composite with better properties is identified as 4% Cu coated CFs reinforced AMMC. When compared with as-cast alloy and Ni coated CF reinforced composite, the tensile strength of Cu coated CFs composite was higher by 15.36% and 2.55%. Similarly, micro-Vickers hardness was improved by 7.61% and 3.09%, impact strength by 19.61% and 3.39%, flexural strength by 87.50% and 15.38%. The corrosion rate (mils/year) was reduced with incorporation of 4% Cu coated CFs in AA6026 by 59.72% and 23.23% as compared with as-cast and Ni coated CF reinforced composition.